Addressing Obstetrical Challenges at 12 Rural Ugandan Health Facilities: Findings from an International Ultrasound and Skills Development Training for Midwives in Uganda - Christina Kinnevey, MD; Michael Kawooya, PhD; Tonny Tumwesigye, MPH; David Douglas, MD; Sarah Sams, MD (Global Health and Education Projects, Inc., 2016)
Background: Like much of Sub-Saharan Africa, Uganda is facing signifi cant maternal and fetal health challenges. Despite the fact that the majority of the Uganda population is rural and the major obstetrical care provider is the midwife, there is a lack of data in the literature regarding rural health facilities' and midwives' knowledge of ultrasound technology and perspectives on important maternal health issues such as deficiencies in prenatal services. Methodology: A survey of the current antenatal diagnostic and management capabilities of midwives at 12 rural Ugandan health facilities was performed as part of an international program initiated to provide ultrasound machines and formal training in their use to midwives at antenatal care clinics. Results: The survey revealed that the majority of pregnant women attend less than the recommended minimum of four antenatal care visits. There were signifi cant knowledge defi cits in many prenatal conditions that require ultrasound for early diagnosis, such as placenta previa and macrosomia. The cost of providing ultrasound machines and formal training to 12 midwives was $6,888 per powered rural health facility and $8,288 for non-powered rural health facilities in which solar power was required to maintain ultrasound. Conclusions and Global Health Implications: In order to more successfully meet Millennium Development Goal 4 (reduce child mortality), 5 (improve maternal health) and 6 (combat HIV) through decreasing maternal to child transmission of HIV, the primary healthcare provider, which is the midwife in Uganda, must be competent at the diagnosis and management of a wide spectrum of obstetrical challenges. A trained ultrasound-based approach to obstetrical care is a cost effective method to take on these goals. Key words: Ultrasound • Uganda • Maternal Health • Fetal Health • Rural • Sub-Saharan Africa • Antenatal Care Copyright © 2016 Kinnevey et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.